2009
DOI: 10.1590/s1676-06032009000400020
|View full text |Cite
|
Sign up to set email alerts
|

The amphibians of São Paulo State, Brazil amphibians of São Paulo

Abstract: Abstract:The State of São Paulo is one of the most studied regions of Brazil in regard to amphibian species richness and distribution. However, we still do not have a list of species for the State. Therefore, we present here a list including 231 species of amphibians (225 anurans and six caecilians), of which 27 are endemic. We present data about previous and current taxonomists and speculate about future prospects in the study and conservation of amphibian biodiversity in São Paulo State. Resumo: O Estado de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 18 publications
0
17
0
7
Order By: Relevance
“…x-signatus which we do not consider as a leaf litter inhabitant). Most of those species are typical constituents of anuran communities in the leaf litter floor of Atlantic Forest areas in southeastern Brazil (e.g., ROCHA et al 2000, ALMEIDA-GOMES et al 2008, SIQUEIRA et al 2009, ARAÚJO et al 2009). However, the hylodid C. aeneus is typically found in association with streams (JORDÃO-NOGUEIRA et al 2006), and the only individual recorded during our study was found in a plot set ca.…”
Section: Resultsmentioning
confidence: 99%
“…x-signatus which we do not consider as a leaf litter inhabitant). Most of those species are typical constituents of anuran communities in the leaf litter floor of Atlantic Forest areas in southeastern Brazil (e.g., ROCHA et al 2000, ALMEIDA-GOMES et al 2008, SIQUEIRA et al 2009, ARAÚJO et al 2009). However, the hylodid C. aeneus is typically found in association with streams (JORDÃO-NOGUEIRA et al 2006), and the only individual recorded during our study was found in a plot set ca.…”
Section: Resultsmentioning
confidence: 99%
“…Tadpoles of this Centrolenidae species were collected in stream stretches located on Santa Marta Farm (CG1) and at Dog (CG2), outside the area destined to the Biological Reserve of Japi Mountain. From the data published by Ribeiro et al (2005) and Araújo et al (2009), it is verified that Japi Mountain contributes to the preservation of approximately 14% (31 out of 225 species) of anuran amphibians recorded in São Paulo state (Table 4).…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, this record extends the known distribution of H. caingua in 155 km (linear distance) northward from the nearest occurrence in Mato Grosso do Sul state, recorded in the municipality of Naviraí (Aoki et al, 2010). Despite the limited knowledge about the biology and ecology of H. caingua (e.g., Melo et al, 2007;Kolenc et al, 2008;Brassaloti et al, 2010), the species appears to be predominantly associated with the Atlantic Forest domain in the São Paulo state (Araújo et al, 2009;Condez et al, 2009;Rossa-Feres et al, 2011). However, the species had already been recorded in open area formations in São Paulo state, i.e.…”
Section: Discussionmentioning
confidence: 99%